The Role of Intergovernmental Fiscal Transfers in Improving Education Outcomes - Al-Samarrai, Samer; Lewis, Blane (Washington, DC: World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.